Oil and Gas Well Brines for Dust Control on Unpaved Roads – Part 1: Ineffectiveness - Payne, Bryce F. (European Scientific Journal, ESJ, 2018)
Natural gas and oil drilling have expanded rapidly in the U.S in recent years. The volume of various associated waste products has been increasing. One such waste product is the typically saline water produced from the wells along with the hydrocarbons. A variety of methods are currently being employed to dispose of this oil and gas well brine (OGB). One such practice is spreading OGB on unpaved roads for dust control and road stabilization. This investigation focused on the likely effectiveness and anticipatable risks of spreading OGB on unpaved roads. Despite decades of regulated use of OGB for dust control, there appears to be a complete lack of data indicating the practice is effective. Analysis of regulations, related literature, and original data indicated spreading OGB on unpaved roads is ineffective and likely counterproductive for dust control and road stabilization as reported here in Part 1, and presents numerous potential and immediate environmental, health and economic risks as reported in Part 2 (publication pending).